2018
DOI: 10.3390/ijms19103157
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dental Prosthesis and Restorative Materials Interface on Oral Biofilms

Abstract: Oral biofilms attach onto both teeth surfaces and dental material surfaces in oral cavities. In the meantime, oral biofilms are not only the pathogenesis of dental caries and periodontitis, but also secondary caries and peri-implantitis, which would lead to the failure of clinical treatments. The material surfaces exposed to oral conditions can influence pellicle coating, initial bacterial adhesion, and biofilm formation, due to their specific physical and chemical characteristics. To define the effect of phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
117
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(128 citation statements)
references
References 116 publications
(153 reference statements)
2
117
0
9
Order By: Relevance
“…Biofilm formation in the oral cavity is a gradated process, consisting of four stages, of which the initial bacterial adhesion and colonization are crucial steps (Hao et al, 2018).…”
Section: ])mentioning
confidence: 99%
“…Biofilm formation in the oral cavity is a gradated process, consisting of four stages, of which the initial bacterial adhesion and colonization are crucial steps (Hao et al, 2018).…”
Section: ])mentioning
confidence: 99%
“…The physical and chemical characteristics of each material influence the pellicle and biofilm formation and might also have an influence on HAP deposition [35]. Comparisons between all materials showed that ceramic samples had the smallest quantity of HAP accumulated after 2 h (Figure 7), while the PMMA samples presented higher numbers of particles and clusters after the same time (Figure 8).…”
Section: Hydroxyapatite Adhesion Efficacymentioning
confidence: 99%
“…It was reported that zirconium-niobium (Zr-Nb) alloys possessed better corrosion resistance and similar biocompatibility compared to Ti-6Al-4V and pure Ti [8,9]. Moreover, some new studies have shown that bacteria attached to zirconium implants poorly compared to titanium ones [10].…”
Section: Introductionmentioning
confidence: 99%